Lab to farm: mapping knowledge transfer channels and determinants from researchers’ perspective – A systematic literature review - Sarra Ben Farah; Nabil Amara (Journal of Innovation & Knowledge)
The literature on the research–practice gap in agriculture has evolved significantly in recent decades. Although there is a well-established body of work on how farmers adopt agricultural research outcomes and the factors that influence their adoption, research on how researchers perceive the process of transferring their results to practical applications, along with the factors that facilitate or hinder this process, remains inadequate. This study addresses this gap by conducting a systematic literature review of empirical studies on knowledge transfer and its determinants from the perspective of agricultural researchers, covering publications from 1960 to 2024. It offers two key contributions: first, an original taxonomy of the channels through which agricultural research is transferred to farmers, and second, an integrative conceptual framework that links knowledge transfer to three categories of influential factors, related to researchers’ individual characteristics, the organizational context within research institutions, and the external environment. Based on the findings, a research agenda has been developed to serve as a foundation for future investigations into persistent gaps in the field. The findings hold value for both academic and practitioner communities as they provide deeper insights to improve the understanding and practice of knowledge transfer in agriculture.